2004
DOI: 10.1097/01.jom.0000121153.55726.95
|View full text |Cite
|
Sign up to set email alerts
|

Study on Musculoskeletal Disorders in a Machinery Manufacturing Plant

Abstract: Musculoskeletal disorders and related risk factors in machinery manufacturing were investigated using interviews, postural analysis, and the revised National Institute for Occupational Safety & Health lifting equation. Sixty-nine workers involved in manual materials handling (Job A) and 51 machinery workers less involved with manual material-handling tasks (Job B) were studied. Low back pain (LBP) (at least one episode lasting for 24 hours or more in past 12 months) prevalence rates were 63.8% and 37.3% for Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
3
9
0
2
Order By: Relevance
“…Studies have shown that prolonged standing is associated with discomfort and cardiovascular problems and have postulated the benefits of changing posture while working 22 . Back pain can also be related to working in standing positions, and to activities which require lifting/carrying loads and repetitive movements of the upper limbs 23,24 . Neck, shoulder and upper limb pain have been related to work activities which require holding the neck in a forward bent posture for a prolonged time, working with arms above shoulder level and repetitive movements of hands and wrists 25,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that prolonged standing is associated with discomfort and cardiovascular problems and have postulated the benefits of changing posture while working 22 . Back pain can also be related to working in standing positions, and to activities which require lifting/carrying loads and repetitive movements of the upper limbs 23,24 . Neck, shoulder and upper limb pain have been related to work activities which require holding the neck in a forward bent posture for a prolonged time, working with arms above shoulder level and repetitive movements of hands and wrists 25,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to MMH tasks, especially manual lifting, is recognized as a major cause of injury in general and an important contributor to the etiology of low-back disorders in particular (NIOSH, 1981;Ayoub and Mital, 1989;Riihimaki, 1991;Skovron, 1992;Mirka and Marras, 1993;Burdorf and Sorock, 1997;Xiao et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The vast majority of the publications were published in English. Three documents (Chen & Yang, 2006; Xiao, Lei, Dempsey, Ma, & Liang, 2004; Xiao & Liang, 2008) were published in a Chinese scientific journal. One article was published in a Dutch journal (Vink, Smitt, & Van Den Berg, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 studies, 3 utilized an existing injury database collected in the field for an analysis of the relationship between the LI and health/injury outcomes (Marras, Fine, Ferguson, & Waters, 1999; Sesek, Gilkey, Drinkaus, Bloswick, & Herron, 2003; Yeung et al, 2003). Individual or grouped LI data were used for associating the LI values with health outcomes in the remaining studies (Garg et al, 2014; Kapellusch et al, 2014; Kucera et al, 2009; Lu et al, 2014; Schneider, Grant, Habes, & Bertsche, 1997; Wang et al, 1998; Waters et al, 1999; Waters et al, 2011; Xiao, Dempsey, Lei, Ma, & Liang, 2004). As seen in Table 1, the RNLE studies were conducted primarily in the manufacturing and wholesale and retail trade (WRT) sectors.…”
Section: Resultsmentioning
confidence: 99%